Barriers and Policy Drivers to Energy Efficiency in Energy Intensive Turkish Industrial Sectors - Kalangos, Constantine (International Journal of Energy Economics and Policy, 2017)
This article investigates the barriers and policy drivers to energy efficiency (EE) in the Turkish automotive, chemicals and textile industries. Contrary to analogous studies, a two-folded research methodology is advanced on the barriers to EE. Besides a survey assessing industrial corporate variables on EE, a market analysis tests the strengths and limitations of additional relevant market actors and of the institutional structure in which they operate. This approach avoids the subjectivity of field respondents in revealing meso and macro economic dynamics. Meanwhile, in light with the intertwined nature of the internal and external barriers to EE, it evaluates them in a holistic manner which is imperative to addressing them effectively. The study of the drivers to EE is conducted based on a framework relating the findings on the barriers to best practice EE policies from various national and international sources. Results point to the need for a mutually reinforcing policy structure that tackles the recorded poor behavioural and managerial practices on EE, the lack of private EE capital funds, the inadequate ESCOs' marketplace and energy suppliers' loose EE practices. Keywords: Energy efficiency; Barriers; Industrial energy policy; Turkey JEL Classifications: D220, L200, L520, Q40